Is Spending More Time Outdoors Able to Prevent and Control Myopia in Children and Adolescents? A Meta-Analysis - Li, Dan; Min, Sicheng; Li, Xianxiong (Ophthalmic research, 2024)
Abstract Introduction: Spending more time outdoors was treated as a safe and cost-effective method to prevent and control myopia. While prior research has established an inverse association between outdoor time and the risk of myopia onset, the effect of increasing outdoor time in delaying the progression of myopia remains a subject of debate. The present meta-analysis aimed to assess the relationship between outdoor time and the myopia onset, and further examine whether there is a dose-response relationship between outdoor time and the risk of myopia onset. Meanwhile, perform whether the outdoor time is related to delaying the progression of myopia. Methods: Studies were retrieved from PubMed, Web of Science, Embase, Medline, and the Cochrane Database, spanning from their inception to February 2023. Three cohort studies and 5 prospective intervention studies were included, with a total of 12,922 participants aged 6–16 years. Results: Comparing the highest with the lowest exposure levels of time spent outdoors, the highest outdoor time was strongly associated with a reduced risk of myopia onset (odds ratio [OR]: 0.53; 95% confidence interval [CI]: 0.34, 0.82). A nonlinear dose-response relationship was found between outdoor time and myopia onset risk. Compared to 3.5 h of outdoor time per week, an increase to 7, 16.3, and 27 h per week corresponded with a respective reduction in the risk of myopia onset by 20%, 53%, and 69%. Among children and adolescents who were not myopic, spending more time outdoors significantly slowed down the speed of change in spherical equivalent refractive (weighted mean difference [WMD] = 0.10D, 95% CI: 0.07, 0.14) and axial length (WMD = −0.05 mm, 95% CI: −0.06, −0.03). Among children and adolescents who were already myopic, spending more time outdoors did not slow myopia progression. Conclusions: Overall, spending more time outdoors can prevent the onset of myopia, but it does not seem to slow its progression. Further studies are needed to better understand these trends.